PELATIHAN PEMBUATAN ONLINE MARKETPLACE WARGA AISYIYAH PDA KOTA MALANG - Shanty, Baroya Mila; Irawati, Sandra; Novianti, Khusnul Rofida (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
The industrial revolution 4.0 makes technology the main factor in carrying out various activities, especially with this pandemic, all activities that were originally carried out offline have turned online. Related to this, it is necessary to create an online marketplace platform that can be used for Aisyiyah PDA Malang residents in running their business. Digital marketing socialization and training activities are also embedded so that Aisyiyah residents have an understanding of the knowledge in operating the online marketplace website that has been created. It is hoped that after this service program is carried out, the online marketplace created can be utilized and used optimally.